What are the perceptions of stakeholders on the utility of the nKPIs for Indigenous services?. (30th September 2020) - Finlay, S; Williams, M; Judd, J; Brown, A
Abstract: Background: The Australian Commonwealth Government has introduced national key Performance Indicators, (nKPIs), for Indigenous primary health care services, including Aboriginal Community Controlled Health Organisations (ACCHOs). The nKPIs aim to assist in the monitoring of Indigenous people's health and aid ACCHOs to monitor their service delivery. The nKPI development and its ongoing implementation have involved stakeholders including the Council of Australian Governments; national and jurisdictional ACCHO peak bodies; government departments; software developers, and researchers. While high-level information is available about the nKPIs, there is very little publicly available information about how they were developed and implemented. This presentation discusses perspectives from stakeholders on the development and implementation of the nKPIs. Methods: Stakeholder interviews (n = 15) aimed to understand the utility and appropriateness of the nKPIs and barriers/enablers to implementation. Stakeholders with knowledge of the development, management or reporting of the nKPIs were recruited. The analysis was conducted inductively and deductively and organised using NVivo. Results: The interviews focused on the history of the nKPIs and the context within which these are collected and managed. Several key themes and sub-themes arose from the stakeholder interviews. These themes included the nKPI purpose, development, implementation, and appropriateness. Several interviewees considered the nKPI development process to be flawed, leading to poor data quality and an increased burden on ACCHOs. Conclusions: The ACCHO sectors' needs and perspectives were mostly ignored in the development process. Numerous research papers and government documents highlight the need for active engagement of Indigenous people to be actively engaged in the design of policies, programs, and frameworks seeking to improve the health of Indigenous people. Key messages: The nKPI implmentation issues could have been avoided had they been developed in partnership with Indigenous organisations. Indigenous policy development needs to be developed in partnership with Indigenous people.